It Matters! Engage. Participate. Vote.: Deciphering the Ballot - Sonoma State University Library (Sonoma State University)
A panel by Students from Political Science 484. In addition to the Presidential election there are many important initiatives on the ballot. Students from Political Science 484 shed light on the most important ones. The discussion was held in the University Library, Jean & Charles Schulz Information Center on the SSU campus.